Solid Phase Extraction of Iron Using 2’-Pyridyliminosalicyl Cellulose - Pandey, H.K.; Vashistha, M.; Bhojak, N. (Asian Journal of Chemistry, 2010)
2´-Pyridyliminosalicyl cellulose has been used for the adsorption and estimation of iron by both column and batch techniques. The distribution coefficient has been determined for iron. Methods have been developed to estimate iron in medicinal tablets.